2021
DOI: 10.1016/j.prostaglandins.2021.106549
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of 2-((3-(chloromethyl)benzoyl)oxy)benzoic acid in LPS-induced rat model

Abstract: Introduction: Salicylic acid derivate is very popular for its activity to suppress pain, fever, and inflam ma tion. One of its derivatives is acetylsalicylic acid (ASA) wh ich has be en reported repeatedly that, as a nonsteroidal anti-inflam ma tory drug (NSAID), it has a cardioprotective effect. Although ASA has various advantages, several stud ies have reported that it ma y indu ce severe peptic ulcer disease. We recently synthesized a new compoun d derived from salicylic acid, name ly 2-((3-(chloromethyl)be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…As a result, it induces acute inflammation in multiple organs, including the kidney, brain, lung, and liver [ 43 ]. Thus, several studies have investigated the anti-inflammatory effects of natural products, compounds, or drugs using LPS-induced animals as models of acute inflammation [ 44 , 45 , 46 , 47 ]. Recently, we reported that the partial replacement of SFAs in a high-fat diet (HFD) with PUFAs such as perilla oil (PO) or corn oil at a converted dose (2–8%) suppressed insulin resistance and nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) signaling pathways, and enhanced antioxidant enzyme expression in rats [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it induces acute inflammation in multiple organs, including the kidney, brain, lung, and liver [ 43 ]. Thus, several studies have investigated the anti-inflammatory effects of natural products, compounds, or drugs using LPS-induced animals as models of acute inflammation [ 44 , 45 , 46 , 47 ]. Recently, we reported that the partial replacement of SFAs in a high-fat diet (HFD) with PUFAs such as perilla oil (PO) or corn oil at a converted dose (2–8%) suppressed insulin resistance and nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) signaling pathways, and enhanced antioxidant enzyme expression in rats [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning, pasta was prepared and then turned into a solution when irradiated by microwaves, and the final product was solid. The synthesis procedure followed the previous experiment, and the stability of 3CH 2 Cl was proven. , Based on these reasons, the compound 3CH 2 Cl can be used for tablet formulation.…”
Section: Methodsmentioning
confidence: 96%
“…The synthesis procedure followed the previous experiment, and the stability of 3CH 2 Cl was proven. 1 , 2 Based on these reasons, the compound 3CH 2 Cl can be used for tablet formulation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations